2014
DOI: 10.3382/ps.2013-03438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low ambient temperatures and dietary vitamin C supplement on growth performance, blood parameters, and antioxidant capacity of 21-day-old broilers

Abstract: The study was conducted to determine the effects of low ambient temperature (LAT) and a vitamin C (VC) dietary supplement on the growth performance, blood parameters, and antioxidant capacity of 21-d-old broilers. A total of 400 one-day-old male Cobb broilers were assigned to 1 of 4 treatments as follows: 1) LAT and a basal diet; 2) LAT and a basal diet supplemented with 1,000 mg of VC/kg (LAT + VC); 3) normal ambient temperature (NAT) and a basal diet; 4) NAT and a basal diet supplemented with 1,000 mg of VC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
6
18
2
Order By: Relevance
“…Results of the present study revealed that the cold-exposed birds consumed more feed but were unable to gain weight and were, therefore, presented with poor FE. Regarding the effects of CS on growth performance our findings reiterated the findings of previous reports in broilers (Ipek and Sahan, 2006;Blahova et al, 2007;Yang et al, 2014). Greater FC of the cold-exposed broilers may be a result of increased metabolic rate resulting from hyper activation of HPT axis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Results of the present study revealed that the cold-exposed birds consumed more feed but were unable to gain weight and were, therefore, presented with poor FE. Regarding the effects of CS on growth performance our findings reiterated the findings of previous reports in broilers (Ipek and Sahan, 2006;Blahova et al, 2007;Yang et al, 2014). Greater FC of the cold-exposed broilers may be a result of increased metabolic rate resulting from hyper activation of HPT axis.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, with an increase in performance, sensitivity of the bird also increased tremendously particularly towards the heat and cold (Burkholder et al, 2008). Although most of the poultry is raised in environmentally-controlled sheds however, maintaining the thermal comfort zone (TCZ) for optimum growth is quite costly (Yang et al, 2014). During the growth phase, TCZ of broilers has a narrow range of 18-22°C.…”
Section: Introductionmentioning
confidence: 99%
“…Cold stress is a physical environmental stressor which affects performance, health and welfare of broiler chicks and thus has a significant impact on the poultry industry (Sato et al, 2002;Hangalapura, 2006;Huff et al, 2007;Yang et al, 2014). This study demonstrates that cold stress predisposes broiler chicks to necrotic enteritis.…”
Section: Discussionmentioning
confidence: 82%
“…The effect of cold stress on the performance, hypertension syndrome, welfare and immune system in broiler chicks has been well documented (Sato et al, 2002;Hangalapura et al, 2003Hangalapura et al, , 2004Hangalapura, 2006;Özkan et al, 2007;Yang et al, 2014). However, the influence of cold stress in relation to necrotic enteritis in a well-established, experimental infection model has not been studied before.…”
Section: Introductionmentioning
confidence: 99%
“…Low ambient temperature caused a significant increase in the RBC count, HB level (MCH and MCHC) (Olanrewaju et al 2010;Yang et al 2014), that is a reflection of physiological oxygentransport capacity. A high value for haematocrit in broilers with a high metabolic rate and under cold stress is an adaptive advantage because the blood's oxygen-carrying capacity is enhanced (Ipek & Sahan 2006).…”
Section: Blood Biochemical and Haematological Parametersmentioning
confidence: 99%